home *** CD-ROM | disk | FTP | other *** search
/ Cream of the Crop 20 / Cream of the Crop 20 (Terry Blount) (1996).iso / math / alged34.zip / ALGED.AE < prev    next >
Text File  |  1996-06-06  |  2KB  |  53 lines

  1. ;
  2. ;  A non-visible comment starts with a semicolon.  If you load a file in
  3. ;  Alged and save it, all your non-visible comments are LOST!  So don't
  4. ;  be too prolific.
  5. "
  6. "   These two functions demonstrate graphics. (Press 'g' twice for 3D).
  7. cos(x*2)^2*cos(y*2)^2 + r*0.2
  8. cos(2*t) + sin(3*t + 0.2*u)
  9. "
  10. "   Solve this for x.
  11. (x*(5 + 2*x) - 2)/(3 + x) - 2*x + 1 = 13
  12. "
  13. "   (1) This is a circle located at the origin.
  14. x^2 + y^2 = r^2
  15. "   (2) This is a parabola that intersects the circle at the x axis.
  16. y = a*(r^2 - x^2)
  17. "
  18. "   Complex arithmetic.
  19. i^i = e^(-1*pi/2)
  20. "
  21. "   Expand this with ^N expand, Distribute, Simplify.
  22. (x - 2/3)^3=0
  23. "
  24. "   Factor this with FactrPoly and Simplify.
  25. x^5 + 47*x^4 - 5606*x^3 - 264690*x^2 + 7857621*x + 372616659 = 0
  26. "
  27. "   Join these terms and simplify
  28. a^x^2*a^(2*x)/a/a^(x + 1)
  29. "
  30. "   Simplify this with polynomial long division
  31. (3*x^2 + 5*x*y - 2*y^2)/(x + 2*y)
  32. "
  33. "   Verify each of the following equations
  34. (x^2 - 2)*(x + 1) = x^3 + x^2 - 2*x - 2
  35. 5*x^2 + 13*x - 6 = (5*x - 2)*(x + 3)
  36. (a^-3*b^7/(a^2*b^4))^-2 = a^10/b^6
  37. x^3 - x^2 - 7 = (x^5 + 4*x^4 - 8*x^3 - 4*x^2 - 35*x + 21)/(x^2 + 5*x - 3)
  38. (1 - x^-2)/(x^-1 - 1) = (-1 - x)/x
  39. "
  40. "    Polynomial long division:  put x in the key and press '\'.
  41. (r*x^6 + s*x^5 + t*x^4 + u*x^3 + v*x^2 + w*x + y)/(x^4 + a*x^3 + b*x^2 + c*x + d)
  42. "
  43. " ---------------------------------------------------------------------
  44. "   The following system of equations describes impact of two bodies.
  45. "   Try so solve for cx, cy and o in terms of the other variables.
  46. m2*cy2 - m2*vy2 = 0
  47. m1*cy1 - m1*vy1 = 0
  48. cx1 - cx2 + (o1*y1 - o2*y2) = -1*E*(vx1 - vx2 + (w1*y1 - w2*y2))
  49. w2*I2 + m2*(x2*vy2 - y2*vx2) = o2*I2 + m2*(x2*cy2 - y2*cx2)
  50. w1*I1 + m1*(x1*vy1 - y1*vx1) = o1*I1 + m1*(x1*cy1 - y1*cx1)
  51. m1*vy1 + m2*vy2 = m1*cy1 + m2*cy2
  52. m1*vx1 + m2*vx2 = m1*cx1 + m2*cx2
  53.